The Implementation of Cambridge Curriculum in English Learning at SMP Lazuardi Tursina - Laili, Nur; Rizkiyah, Faiqotur (Universitas Lancang Kuning, 2024)
In Indonesian schools, the curriculum is crucial for teaching-learning process. As a means of improving student competencies and educational quality, certain Indonesian schools are starting to implement overseas curricula, such as Cambridge. However Indonesian schools have different approaches to implementing the Cambridge curriculum. The purpose of this research is to investigate how the Cambridge Curriculum is being used at SMP Lazuardi Tursina for English language instruction. A qualitative strategy using a case study design is the methodology used. Data were gathered using curriculum-related document analysis, interviews, and observations. The results show three important phases to the Cambridge curriculum's application in English learning: planning, implementing, and assessing. With a focus on critical thinking and problem-solving techniques, SMP Lazuardi Tursina combines the Independent and Cambridge curricula. Adapting to Project-Based Learning and Learning Experience Design, as well as instructor turnover, are implementation challenges. The learners' progress and performance were assessed using the Check Point and Cambridge Progression Tests. The findings highlight how important the phases of the Cambridge curriculum implementation are to SMP Lazuardi Tursina's successful adoption of the curriculum. To support student learning outcomes and improve educational quality, the Cambridge curriculum demands careful planning, creative teaching strategies, and thorough evaluation.